Poster: Tackling dust in the workplace - the role of dust lamps in New Zealand - Levinge, Robyn (New Zealand Journal of Health and Safety Practice, 2024)
Problem Dust exposure is evolving from an occupational concern to an emerging public health crisis in New Zealand, impacting a wide range of workplaces. The health implications-from immediate respiratory issues to long-term conditions-underscore the urgency for effective intervention. Study objective: Investigate the use and effectiveness of dust lamps in New Zealand workplaces for monitoring and mitigating dust exposure. Methodology: Case studies were conducted in diverse New Zealand workplaces with various dust- generating practises to assess dust lamp functionality. An online survey engaged with health and safety practitioners, occupational specialists and other relevant personnel. Results Dust lamps, while not a standalone solution, offer significant promise when integrated into a broader, holistic dust management strategy. They help make invisible dust visible and can be a vital part of a comprehensive approach, provided there is increased awareness, proper training, and broader adoption. To address the current gaps in knowledge and practice, it is crucial for researchers, regulators, and industry stakeholders to collaborate. This will enhance the efficacy of dust lamps, improve overall health outcomes, and ensure that New Zealand's workplaces are safer and healthier for all workers.